Pemikiran Abdullah Ahmad Al-Na’im tentang Larangan Pernikahan Beda Agama dan Implikasinya di Indonesia - Zalsabillah, Annisa; Agung, Muh.; K, Kurniati (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Interfaith marriages are a crucial aspect of human life today. The clash of norms that exist in society makes this even more crucial and triggers the birth of propaganda and complex problems in the lives of Muslim communities, especially when there is an absolute ban on interfaith marriages in Indonesia. This research will examine Abdullah Ahmad An-Na'im's thoughts regarding the permissibility of interfaith marriages and their implications in Indonesia. The type of research used in this research is library research with a theoretical approach to normative Sharia, normative juridical and socio-legal theories. Primary data sources come from Abdullah Ahmad An-Na'im's books and literature/rules discussing interfaith marriages. Meanwhile, secondary data comes from literature or data that supports the object of study, such as journals and so on. The data was then analyzed using exploratory analysis. The results of this research show that Abdullah An-Na'im's thoughts regarding the prohibition of interfaith marriages are a form of religion-based discrimination. So if it is correlated with the situation in Indonesia, interfaith marriage in Indonesia is not appropriate because it imposes a prohibition that is not based on humanism, especially because Indonesia is not an Islamic country. The implication of this research is that the provisions regarding the prohibition of interfaith marriages in Indonesia should be revoked and permitted with exceptions in emergency situations.